(untitled) (Journal of Oriental Studies, 2023)
The article raises the question of paying attention to the extant handwritten treatises of Abu Nasr al-Farabi. The necessity of determining their exact number and full name is emphasized. Attention is also drawn to the fact that a number of al-Farabi’s treatises, which were not included in scientific circulation, have been preserved only in handwritten form. This article defines the total number and titles of handwritten treatises belonging to al-Farabi, stored in the library of Leiden University in the Netherlands, and also clearly indicates their registration numbers in the library. It is noted that among these treatises there is a treatise that has not yet entered scientific circulation and has not been translated into Kazakh.Described in Maqālāt ar-Rafīʿa ʿIlm Uṣūl fī aṭ-Ṭabīʿa (registration number: Or.2930); ʿUyūn al-Masāʾil (registration number: Or.184:13); Fī mā yanbaġī an yuqaddama taʿallum qabla al-falsafa (registration number: Or. 184:7) copies of the first and last pages of these 3 (three) manuscripts of the treatise are attached. During the preparation of the article, methods of collection, grouping, differentiation, comparison, translation from the original, citation, wording, etc. of unique manuscripts belonging to al-Farabi were used. Key words: al-Farabi, manuscript, original text, translation, description.